Bond graph based control of a solar array. (December 2018) - Tapia Sánchez, Roberto; Medina Ríos, J. Aurelio; Paz, Antonio Ramos
In this paper, the control of a solar array is proposed. The bond graph methodology is applied in order to get the structure control law for a solar array connected to the electrical network. For this, the different models of the complete system are presented. The solar array is built up by considering the individual solar panels. The inverter bond graph model is used for the development of the proposed control law. This model is inverted graphically to get the control structure. Also, the Park transformation concept is adapted to handle the control structure. This allows us to get a different control structure. Two different controls are considered in the proposed control structure, with their robustness tested for different power factors. The control law is tested using a real-time simulator. For this test, the rapid control prototyping concept is used. The obtained results demonstrate the viability of the proposed control law.